2021
DOI: 10.1016/j.ahjo.2021.100011
|View full text |Cite
|
Sign up to set email alerts
|

Sex and gender differences in COVID-19: More to be learned!

Abstract: The COVID-19 pandemic has affected millions of patients across the globe. Multiple studies, national and international governmental data have shown important sex and gender differences in the incidence and outcomes of patients with COVID-19. These differences are not only attributed to the differences in age and comorbid conditions but likely a combination of factors, including hormonal differences, immune response, inflammatory markers and behavioral attitudes, among others. In this review, we discuss the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 30 publications
4
68
1
1
Order By: Relevance
“…In this sense, the double copy of the X chromosome in females is essential against viral infections. However, it is observed that female are at a higher risk of COVID-19 clinical manifestations in the long term than males [43].…”
Section: Discussionmentioning
confidence: 97%
“…In this sense, the double copy of the X chromosome in females is essential against viral infections. However, it is observed that female are at a higher risk of COVID-19 clinical manifestations in the long term than males [43].…”
Section: Discussionmentioning
confidence: 97%
“…Sex and gender strongly influence the severity and mortality of the disease, which hare higher in men than in women across the lifespan [ 41 , 42 , 43 ]. COVID-19 is more devastating in old men [ 53 ], who have a higher risk for intensive care unit admissions and mechanical ventilation [ 65 ]. Further, men die twice as much compared with women [ 65 ].…”
Section: Sex and Gender Aspects In Covid-19mentioning
confidence: 99%
“…COVID-19 is more devastating in old men [ 53 ], who have a higher risk for intensive care unit admissions and mechanical ventilation [ 65 ]. Further, men die twice as much compared with women [ 65 ]. The higher rates of mortality or severity in men are still present after adjusting for comorbidities.…”
Section: Sex and Gender Aspects In Covid-19mentioning
confidence: 99%
See 2 more Smart Citations